Statement by the Managing Director on the Work Program of the Executive Board Executive Board Meeting November 4, 2009. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Fund, called on to support a global response to the global crisis, has delivered with strengthened surveillance, policy advice and financing with modernized instruments. As I noted in Istanbul, where the membership expressed its appreciation for these accomplishments, we need to focus in the months ahead on four key reform areas-the Istanbul decisions, namely our mandate, our financing role, multilateral surveillance, and governance-while supporting the consolidation of the nascent upturn and helping to establish a stronger post-crisis global economy. Building on the work that we have completed in recent months (Table 1), the noncountry work program set out in Table 2 (which leaves aside country items such as Article IVs and program reviews) aims to accomplish these objectives. This work program is no less ambitious and taxing than the one we have just completed, but I am sure that we can successfully meet this challenge.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet